306 Intraoral Spectroscopy for the Identification and Study of Molar Hypomineralization - Sarah Boyer; Ray Jurado; Ashlee Cosantino; Azza Ahmed; Derk Joester (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Molar hypomineralization (MH) is a highly prevalent dental disease that leads to rapid enamel decay even with preventative measures. While the harm is apparent, the etiology of the condition is not. Further, MH is difficult to study due to limited intact extracted teeth. Therefore, we need a method to study MH non-destructively and intraorally. METHODS/STUDY POPULATION: Recent work has shown excess proteins not commonly found in enamel are present in teeth with MH. This is theorized to be due to disruption and infiltration in the cells that form enamel leading to leftover protein and under mineralized enamel. We hypothesizethese proteins have specific spectroscopic signatures that can be detected using light. We further hypothesize that modern fiber optic probes can provide a method for non-destructive, pain-free, and rapid intraoral examination of MH. Initially, Micro Raman spectroscopy was used to detect specific vibrational bands associated with organics in teeth with MH followed by the collection of spectra of teeth with MH and heathy enamel using a spectrophotometer. These spectra were examined for any obvious differences. RESULTS/ANTICIPATED RESULTS: Currently 12 teeth were collected, and micro-computed tomography reconstructions confirmed location in 3D of MH lesions. Micro Raman of a MH-affected tooth revealed clear organic associated Amide I and III vibrational bands when compared to a synthetic hydroxyapatite (mineral in enamel) powder standard. We determined the wavelength of light that can be used to detect spectral differences between healthy enamel and teeth with MH. The next steps include optimization of the protocol of the intraoral spectrometer with the determined wavelength for implementation in clinic to allow for collection of spectra without the need for tooth extraction. DISCUSSION/SIGNIFICANCE: We hope that this work will lead to advancements in our understanding of the mechanism of MH as well as act as a proof of concept for a MH diagnostic tool. In the long term, the goal is to ideally lead to improvements in dental health care, decrease dental costs, and improve overall quality of life for the children with this condition.